The Magical Journey of Logistics: Maximizing Efficiency with Digital Information Technology - Anisa, Resha Yanur; Adman, Adman (Universitas Pendidikan Indonesia, 2024)
Information technology and digitalization are crucial in the logistics sector today, offering various advantages. However, significant challenges and limitations remain in the process of digitalization. This study aims to clarify the role of digitalization in enhancing logistics performance and the opportunities and challenges faced by logistics companies in this digital era. Employing a qualitative method with a literature review approach, this research relies on secondary data. The findings indicate that digitalization is vital for inventory management, planning, implementation, and controlling the flow of goods and services. It serves as an effective tool for monitoring logistics status and improving performance in terms of efficiency, effectiveness, and differentiation. Nevertheless, challenges such as cyberattacks, issues with goods not reaching their destinations, scalability of organizational structures, and the reliability of information must be addressed to fully leverage the benefits of digitalization in logistics.